A framework for reviving traditional handicrafts: Craft branding, product development, and marketing strategies for dong ethnic craft in Sanjiang, China - Liang Xianfei; Zairul Anuar Md. Dawam (Center for Cities, University of Moratuwa, Sri Lanka, 2024)
The traditional Dong handicrafts of Sanjiang, rooted in the cultural heritage of the Dong ethnic group face challenges in retaining their market relevance while preserving their traditional characteristics. Despite their cultural and historical significance, these handicrafts struggle to meet the growing demands of the modern cultural and creative industries, leading to declining sales. This study examines the traditional handicrafts of the Dong community in China. It produces a theoretical framework that can be applied to revitalize them by focusing on three key areas: product development, craft branding and marketing strategies. The paper specifically explores traditional practices such as textile dyeing, wooden architecture construction, and silver craftsmanship, highlighting their cultural and economic importance in contemporary contexts. This research employs a case study method. Data collection process involved gathering and analyzing information from academic journals, government reports, and published magazines. It concludes that the marketability of Dong handicrafts could be enhanced through the development of innovative craft branding strategies that integrate traditional craftsmanship with modern design and technologies while safeguarding their cultural heritage. By employing insights from product development branding and marketing strategies, the paper proposes solutions to revitalize and sustain Dong handicraft traditions in the face of modernization and globalization. The research confirms that traditional Dong handicrafts, despite facing challenges from modernization, globalization, and technological advancements, can be revitalized through the strategic application of product development, branding and marketing frameworks.